Development of a gas chamber for detecting broiler chicken halothane sensitivity and PSE (Pale, Soft, Exudative) meat formation - Marchi,Denis Fabrício (2009)
The objective of this work was to investigate the use of a halothane to screen broiler chickens prone to develop PSE (Pale, Soft, Exudative) meat through a special gas chamber connected to a veterinarian anaesthetic apparatus developed in our laboratory. Anaesthesia was induced with approx. 3.0% halothane at a flow rate of 6.0 Lm-1 in pure oxygen for 5 min. Commercial male broilers (n=342) aged 46 days old were evaluated and classified as either halothane sensitive (HAL+) or insensitive (HAL-), depending on the leg rigidity response. Approximately 27.5% (n=94) of broilers were HAL+ and 72.5% (n=248) were HAL-. This is a simple and rapid technique to evaluate broiler sensitivity to halothane and identify broilers prone to develop PSE meat. The occurrence of PSE meat in HAL insensitive broiler chicken samples suggests that other factors are related to PSE occurrence.